A compact UWB antenna with reconfigurable dual notch bands. Issue 12 (December 2015) - Srivastava, Gunjan; Dwari, Santanu; Kanaujia, Binod Kumar
ABSTRACT To effectively utilize the entire ultrawideband (UWB) spectrum in case of no interference scenarios, a UWB antenna having reconfigurable dual band notch characteristics at WiMAX and WLAN band of frequencies is presented in this article. The p‐i‐n diodes and capacitors are properly placed in the UWB antenna to achieve the reconfigurable band notch function. The proposed antenna has the wide impedance bandwidth of 8 GHz (from 2.7 to 10.7 GHz). The four possible combinations of three p‐i‐n diodes are used to obtain single/dual reconfigurable notch bands in entire UWB band. The rejected WiMAX and WLAN band of frequencies are centered at 3.6 GHz and 5.5 GHz, respectively. The size of the proposed antenna is 27 × 32 mm2. The measured results are in good agreement with the simulated results. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:2737–2742, 2015